Remote continental aerosol characteristics in the Rocky Mountains of Colorado and Wyoming - Levin, Ezra JT, author; Kreidenweis, Sonia M., advisor; Collett, Jeffrey L., committee member; van den Heever, Susan C., committee member; Ham, Jay, committee member (Colorado State University. Libraries, 2013)
The Rocky Mountains of Colorado and Wyoming enjoy some of the cleanest air in the United States, with few local sources of particulate matter or its precursors apart from fire emissions, windblown dust, and biogenic emissions. However, anthropogenic influences are also present with sources as diverse as the populated Front Range, large isolated power plants, agricultural emissions, and more recently emissions from increased oil and gas exploration and production. While long-term data exist on the bulk composition of background fine particulate matter at remote sites in the region, few long-term observations exist of aerosol size distributions, number concentrations and size resolved composition, although these characteristics are closely tied to important water resource issues through the potential aerosol impacts on clouds and precipitation. Recent modeling work suggests sensitivity of precipitation-producing systems to the availability of aerosols capable of serving as cloud condensation nuclei (CCN); however, model inputs for these aerosols are not well constrained due to the scarcity of data. In this work I present aerosol number and volume concentrations, size distributions, chemical composition and hygroscopicity measurements from long-term field campaigns. I also explore the volatility of organic material from biomass burning and the potential impacts on aerosol loading. Relevant aerosol observations were obtained in several long-term field studies: the Rocky Mountain Atmospheric Nitrogen and Sulfur study (RoMANS, Colorado), the Grand Tetons Reactive Nitrogen Deposition Study (GrandTReNDS, Wyoming) and as part of the Bio-hydro-atmosphere interactions of Energy, Aerosols, Carbon, H2O, Organics & Nitrogen project (BEACHON, Colorado). Average number concentrations (0.04 < Dp < 20 μm) measured during the field studies ranged between 1000 - 2000 cm-3 during the summer months and decreased to 200 - 500 cm-3 during the winter. These seasonal changes in aerosol number concentrations were correlated with the frequency of events typical of new particle formation. Measured sub-micron organic mass fractions were between 70 - 90% during the summer months, when new particle formation events were most frequent, suggesting the importance of organic species in the nucleation or growth process, or both. Aerosol composition derived from hygroscopicity measurements indicate organic mass fractions of 50 - 60% for particles with diameters larger than 0.15 μm during the winter. The composition of smaller diameter particles appeared to be organic dominated year-round. High organic mass fractions led to low values of aerosol hygroscopicity, described using the κ parameter. Over the entire year-long BEACHON study, κ had an average value of 0.16 ± 0.08, similar to values determined during biologically active periods in tropical and boreal forests, and lower than the commonly assumed value of κcontinental = 0.3. There was also an observed increase in κ with size, due to external mixing of the fine mode aerosol. Incorrect representations of κ or its size dependence led to erroneous values of calculated CCN concentrations, especially for supersaturation values less than 0.3%. At higher supersaturations, most of the measured variability in CCN concentrations was captured by changes in total measured aerosol number concentrations. While data from the three measurement sites were generally well correlated, indicating similarities in seasonal cycles and in total number concentrations, there were some variations between measurements made at different sites and during different years that may be partly due to the effects of local emissions. The averaged data provide reasonable, observationally-based parameters for modeling of aerosol number size distributions and corresponding CCN concentrations. Field observations clearly indicated the episodic influence of wildfire smoke on particle number concentrations and compositions. However, the semi-volatile nature of the organic carbon species emitted makes it difficult to predict how much of the emitted organic mass will remain in the condensed phase downwind. To better constrain the volatility of organic species in smoke, emissions from laboratory biomass combustion experiments were subjected to quantified dilution, resulting in reduction of aerosol mass concentrations over several orders of magnitude and a corresponding volatilization response of the organic particles that was fit to the commonly-applied Volatility Basis Set. Organic emissions from all burns with initial organic aerosol concentrations greater than 1000 μg m-3 contained material with saturation concentration values ranging between 1 and 10,000 μg m-3, with most of the organic mass falling at the two extremes of this range. For most burns, a single distribution was able to capture the volatility behavior of the organic material, within experimental uncertainty, despite the considerable variability in fuel and fire characteristics, suggesting that a simplified two-product model of gas-aerosol partitioning may be adequate to describe the evolution of biomass burning organic aerosol in models.
Keywords: aerosol; smoke; new particle formation; CCN